Analysis of Seventh-Grade Students’ Performance in National Mathematics Competitions by Topic and Task Type: A Comparison of Specialized and Regular Classes - Milenković, Aleksandar; Milikić, Milan; Vulović, Nenad (Studies in Teaching and Education, 2025)
Mathematics competitions are increasingly attracting the researchers’ attention in the field of mathematics education, as they offer numerous benefits to students — from deepening and broadening their knowledge to developing problem-solving skills. Given that seventh-grade students in the Republic of Serbia have, for many years had, the opportunity to attend specialized classes for mathematically gifted students (SM classes), the question arises whether grouping these students in homogeneous classes affects their performance in national mathematics competitions. The aim of this paper is to make a detailed comparison of the performance of students from SM and regular classes in the national competitions and to analyze the tasks in which the two groups statistically significant differences. The analysis of students’ performance in 50 competition tasks showed that SM students achieved statistically significantly better results in 23 tasks,while the students from the regular class only performed better in one task. Greatest differences in favor of SM students were observed in number theory, followed by geometry and combinatorics, with the smallest differences in algebra tasks. SM students were significantly more successful in solving proof-based tasks than their peers from regular classes. A detailed analysis of tasks content suggests that the differences in performance may be due to the broader and deeper mathematical education that SM students have, as well as their superior ability to synthesize various mathematical concepts and statements in the problem-solving process. The results of this study can serve as a guide for both teachers and students in preparing for mathematics competitions.
Keywords: mathematics competitions; type of class; mathematical topics; task type; student performance